Acetone–butanol–ethanol competitive sorption simulation from single, binary, and ternary systems in a fixed‐bed of KA‐I resin. (24th November 2014) - Wu, Jinglan; Zhuang, Wei; Ying, Hanjie; Jiao, Pengfei; Li, Renjie; Wen, Qingshi; Wang, Lili; Zhou, Jingwei; Yang, Pengpeng
<x xml:space="preserve">Abstract</x> Separation of butanol based on sorption methodology from acetone–butanol–ethanol (ABE) fermentation broth has advantages in terms of biocompatibility and stability, as well as economy, and therefore gains much attention. In this work a chromatographic column model based on the solid film linear driving force approach and the competitive Langmuir isotherm equations was used to predict the competitive sorption behaviors of ABE single, binary, and ternary mixture. It was observed that the outlet concentration of weaker retained components exceeded the inlet concentration, which is an evidence of competitive adsorption. Butanol, the strongest retained component, could replace ethanol almost completely and also most of acetone. In the end of this work, the proposed model was validated by comparison of the experimental and predicted ABE ternary breakthrough curves using the real ABE fermentation broth as a feed solution. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:124–134, 2015